On the Inefficiency of Inequality - Schiff, Maurice (World Bank, Washington, D.C., 2013)
A number of studies have examined the implications of preference interdependence. This paper models individual utility as depending either on the level of other people's consumption or on the difference in consumption levels. It assumes that the impact of an increase in other people's consumption on individual utility diminishes with the level of consumption, raising individual utility when that consumption is very small and lowering it when that consumption is very large. Based on that plausible assumption, the paper shows that, whether individual utility depends on the level of other people's consumption or on the difference in consumption levels, i) welfare declines with inequality, ii) equilibrium inequality is inefficient, and iii) the optimal intervention leads to a more equal distribution. Implications for the role of development institutions are examined.